Development of Virtual Laboratory Electronic Student Worksheet Using PjBL to Improve Critical Thinking Ability - Julianti, Beti; Haryadi, Rudi; Oktarisa, Yuvita (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2023)
The use of virtual laboratories is a solution for schools that have not been able to carry out practical activities directly. This study aims to develop virtual laboratory electronic student using PjBL which can improve students' critical thinking ability. The research method used is the research and development (R & D) method with the ADDIE development model (analysis, design, development, implementation, & evaluate). The research subjects used were 30 students of class XII IPA who were selected using a purposive sampling technique. Data collection instruments consist of expert validation sheets, student response questionnaires, and critical thinking ability tests (pretest and posttest). The data analysis techniques used are Likert scale and n-gain analysis. The evaluation of the feasibility of electronic student worksheet by the expert got an average percentage of 85.41% with a very valid category, student test results got a n-gain value of 0.38 with a moderate improvement category, and the results of student responses got an average percentage value of 91.35% in the very good category. Thus, the developed virtual laboratory electronic student worksheet using PjBL can Improve students' critical thinking ability